(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Two notions, freedom and liberty has always been controversial topic in the field of linguo-conceptual study. Although they have similar meanings, several differential meanings can also be identified. The following article is going to analyse a number of idiosyncrasies by exampling “the Statue of Liberty” in American linguo-culture.